The new formal specification framework of individual emergency, response and preparedness - Roslina, Mohd Sidek; Noraziah, Ahmad; Mohd Helmy, Abd Wahab (Elsevier Ltd., 2011)
Competence is a very important characteristic to all area of activity, especially in an emergency situation. This is because people must react according to what supposed to do. In particular, if an individual lacking competence in the job or life, the person may take wrong action and make more loss in the area of work or situation such loss of life, injured, and others. This paper presents a new formal specification framework of individual Emergency, Response and Preparedness (ERP). A chemical company in Pahang, Malaysia has been selected as a case study to model the framework of emergency, response and preparedness. We design the framework of ERP according to the company's competency by considering three elements which are the skill, knowledge and attitude. Furthermore, this framework results the specification becomes clear, sharp, precise and non-multi-interpretation.